Combined Effect of Vaccinium nilgiriensis Bark Extract and 680nm Laser Irradiation in Inducing Breast Cancer Cell Death - George, Blassan P.; Chandran, Rahul; Thamburaj, Suman; Parimelazhagan, Thangaraj (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Cancer refers to a collection of diseases where cells begin to multiply uncontrollably. Breast cancer is the most predominant malignancy in women. Herbal medicine is one of the important health care systems in most developing countries. Many studies have shown that naturally occurring compounds may support the prevention and treatment of various diseases, including cancer. Some of the plant extracts and isolated compounds show photosensitizing activities and reduce cell proliferation whereas some have revealed photoprotective effects. Objectives: The biological properties and medicinal uses of extracts and bioactive compounds from V. nilgiriensis have not been investigated. This study aims to evaluate the cytotoxic effects of V. nilgiriensis in combination with 680nm laser irradiation on MCF-7 breast cancer cells. Methods: The inverted microscopy, ATP and LDH assay were used to analyze the cellular morphology, proliferation, cytotoxicity respectively after the treatment with V. nilgiriensis bark extract. The diode laser of wavelength 680nm and 15 J/cm2 fluency has been used for laser irradiation. The activity of apoptotic proteins was studied using ELISA and nuclear damage by Hoechst staining. Results: The exposure of V. nilgiriensis extracts with laser irradiation at 680nm increases the cytotoxicity and decreases the proliferation of MCF-7 cells. The results of the Hoechst stain indicated nuclear damage. Our study proved that V. nilgiriensis holds a strong cytotoxic effect on breast cancer cells alone and in combination with laser irradiation by upregulating the expression of apoptotic proteins such as caspase 3, p53 and Bax. Conclusion: The results from this study showed that the bark ethyl acetate of V. nilgiriensis and in combination with laser is effective in preventing breast cancer cell proliferation in vitro. Further work is warranted to isolate the bioactive compounds from V. nilgiriensis bark extract and study the effect of compounds in the cell death induction. Due to the cytotoxic properties, V. nilgiriensis can be considered as a potent therapeutic agent for the treatment of cancer.
Keywords: nuclear damage